God and race in American politics : a short history - Noll, Mark A., 1946- (Princeton University Press, 2008)
Religion has been a powerful political force throughout American history. When race enters the mix the results have been some of our greatest triumphs as a nation--and some of our most shameful failures. In this important book, Mark Noll, one of the most influential historians of American religion writing today, traces the explosive political effects of the religious intermingling with race. Noll demonstrates how supporters and opponents of slavery and segregation drew equally on the Bible to justify the morality of their positions. He shows how a common evangelical heritage supported Jim Crow.